Present state of the knowledge of aquatic mollusks in Peru - Paredes, Carlos (1999)
The present state of knowledge on the aquatic mollusks of Peru is reviewed herein. Marine and freshwater mollusks are treated separately, offering information on numbers of families, genera and known species, their geographical distribution, their conservation status and utilization by man. Updated species lists are included.